A water-responsive, gelatine-based human skin model - Dąbrowska, A.; Rotaru, G.M.; Spano, F.; Affolter, Ch; Fortunato, G.; Lehmann, S.; Derler, S.; Spencer, N.D.; Rossi, R.M. (Tribology international, 2017)
The properties of human skin strongly depend on hydration. Skin friction, elasticity and roughness change significantly in the presence of water. This paper presents a new bio-mimicking gelatine-based physical skin model that simulates the frictional behaviour of human skin against a widely-used standard textile under dry and wet conditions and over a broad range of applied normal load (0.5–5N) and amount of water at the interface (0–100μl/cm2). The proposed skin model shows good agreement with the frictional behaviour of human skin both in dry and wet conditions. In addition, the tensile Young's modulus and surface roughness exhibit changes as a function of the amount of water that are similar to those of human skin. Potential applications of the model are in the testing and development of textile materials that mechanically interact with human skin. •A new bio-mimicking gelatine-based physical skin model is proposed.•Gelatine-based skin model responds to water, what influences its properties.•Proposed skin model mimics frictional behaviour of human skin against woven cotton in dry and hydrated conditions.•New skin model follows the decrease in tensile Young's modulus and surface roughness previously reported for the skin.